Pengaruh Plafon Terhadap Tingkat Kenyamanan Penghuni Rumah Tinggal - Arinda Wahyuni; Ahmad Nadhil Edar (LOSARI Jurnal Arsitektur, Kota dan Permukiman, 2021)
Research on "Study of the rate ceiling Occupant Comfort House Live" aims to determine the appropriate standard ceiling height for the convenience of residents, to determine the effect of color on the comfort level of the household, and to find a good material used for the ceiling of the house. The research was conducted using surveys, and the distribution of questionnaires to residents' lives to be studied, namely residents living that have a high ceiling, low, and medium. To achieve these objectives, the research methods used to study "Ceiling Study on Occupant Comfort Level House Live", namely: Observation is one of the methods of data collection techniques that not only measures the attitudes of respondents (interviews and questionnaires) but also can be used to record a variety of phenomena that occur (situation, condition). The questionnaire/questionnaire was conducted with data collection techniques by providing a set of questions or statements to others as respondents to answer. Research using this research tool gauges is distance meter ceiling height. Literature is a data collection technique in which researchers collected data on the theoretical basis associated with the object examined